Determinants of consumer literacy among Universiti Putra Malaysia students - Bashri, Zaim Aizat Akmal; Abu Bakar, Elistina (Human Resource Management Academic Research Society, 2022)
Consumer literacy means whether the consumers can apply the information when making transactions and are more likely to understand how to seek redress. This study aims to determine the factors of consumer literacy among university students. The studied factors were self-efficacy, attitude toward consumerism, peer influence, and the intensity of consumer education. The study also aims to see the difference between those involved in the consumer movement and those who were not. The data was collected from 200 respondents who were chosen through cluster samplings. The multiple regression analysis results showed that self–efficacy, attitude towards consumerism, and the intensity of consumer education (frequency, clarity and effectiveness) explain the 13.0 % variance in consumer literacy. Nevertheless, the peer influence had no significant relationship with consumer literacy. The t-test analysis also found that those students involved in the consumer movement at the university had achieved a good literacy level compared to those not involved. The research gives a significant implication to consumers, government, non-government organizations, and institutions of higher learning to draft a consumer policy for young consumers. Consumer education needs to be systematic and more intense, especially in disseminating information more frequently, clearer, and easily accessible to every consumer.